Virtual prosthetic try in using Photoshop: Method of transferring veneers from the cast to the patient’s mouth digitally - ABYAD, Ahmed; LAWAND, Ghida (International Arab Journal of Dentistry (IAJD), 2020)
Utilizing software to transfer photographic templates of teeth to the patient’s mouth before the treatment is a common practice in esthetically demanding cases; this is termed as a digital smile design. However, transferring the actual restorations from the finalized cast to the patient’s mouth digitally using software before the try-in session is not reported in the literature. The steps and benefits of performing a virtual try-in (VTI) before the fitting try-in session are demonstrated in this article.